Affixations in Javanese Transitive Verbs that Change the Constituents from Divalent to Trivalent (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This paper aims to describe the affixations in Javanese transitive verbs that affect the valency of a sentence from divalent to trivalent. Other studies have explored the grammaticality of transitive verbs’ valency, but none have investigated the details of Javanese verbs’ morphological structure in relation to the phonemic structure. The data are extracted from Javanese transcription of YouTube videos and certain magazine articles. This paper employs a generative qualitative method equipped with various technical analyses. The analysis includes investigations of several forms of affixation in Javanese transitive verbs that result in a shift regarding a sentence’s valency. The analysis continues by addressing similarities in the verb phonemes that exhibit a certain affixation. The findings show at least three forms of prefix, five forms of vowel modification, and two forms of suffixes that can add a sentence’s argument when applied in a specific composition of phonemes.